Reminiscing About 15 Years of Interoperability Efforts - Van de Sompel, Herbert; Nelson, Michael L. (D-Lib magazine, 2015)
Looks back at three efforts in which the authors have been involved that illustrate the evolution of interoperability problems for web-based scholarship over the past 15 years : the Open Archives Initiative Protocol for Metadata Harvesting (OAI-PMH) (1999), the Open Archives Initiative Object Reuse and Exchange (OAI-ORE) (2006), and Memento - Time Travel for the Web. Attempts to characterise the perspectives and technical toolkits that provided the basis for these endeavours. Considers repository-centric and web-centric interoperability perspectives, and the use of a Linked Data or a REST/HATEAOS technology stack, respectively. Laments the lack of interoperability across nodes that play a role in web-based scholarship, but presents some ideas regarding a possible path forward. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.